Implementing IoT-Based Smart Garden System at SMP Al Izhar: Menerapkan Sistem Taman Pintar Berbasis IoT di SMP Al Izhar - Yosy Rahmawati; Achmad Zuchriadi; Ni Putu Devira Ayu Martini; Ayu Mika Sherila (Academia Open, 2025)
General Background: The integration of Internet of Things (IoT) technology in agriculture presents new opportunities for sustainable practices and hands-on education. Specific Background: However, its implementation in junior high school curricula, particularly as a practical environmental learning tool, remains limited. Knowledge Gap: Most schools lack access to real-world IoT-based applications that foster student engagement with digital literacy and environmental awareness simultaneously. Aims: This study aimed to design and implement an IoT-based Smart Garden system for automatic irrigation and lighting at SMP Al Izhar Pondok Labu, while evaluating its educational and technological impacts. Results: The program involved 50 participants who built functional Smart Garden prototypes using sensors and microcontrollers, resulting in significant gains in STEM motivation (+1.1), understanding of IoT (+1.2), and its application in agriculture (+1.2). Novelty: The innovation lies in integrating project-based learning with low-cost IoT hardware to create a replicable educational model that combines STEM skills, environmental education, and digital literacy. Implications: The success of this initiative highlights the potential of IoT-enhanced environmental projects to enrich school-based learning, strengthen 21st-century competencies, and inspire broader adoption of smart, sustainable practices in education.Highlight : The program introduced IoT-based Smart Garden systems to junior high school students through hands-on workshops, fostering practical STEM skills. Students showed a 25% increase in understanding and motivation, based on pre- and post-test assessments, highlighting educational impact. The initiative provides a replicable model for integrating environmental and digital literacy in school curricula, promoting sustainability. Keywords : Automatic Irrigation, Environmental Sustainability, Internet of Things (IoT), Smart Garden, STEM Education